Mahkamah Konstitusi dan Penguatan Konstitusi Ekonomi Indonesia - Harvelian, Agnes (Mahkamah Konstitusi Republik Indonesia, 2016)
existence of the Constitutional Court interpreted as the guardians of the constitution of the various operational policies that are not in accordance with the constitutional mandate. Climate ‘economic’ change is happening the world economy, shift-many policy base the national economy. This study intends to identify and analyze the involvement of the Constitutional Court towards strengthening the Constitutional Foundation of Economical System in Indonesia, which would determine the appropriate policy actualization. Therefore, it is important to identify and analyze the value of the economic constitution of Indonesia that was based on a social contract supreme law, the constitution and the ruling of the Constitutional Court that in the economic field and be able to influence national economic policy. The method of approach used in the study is descriptive analytical that explain and analyze by law as a regulation made by the Indonesian government to national economic policy, which is associated with the actual conditions that occur. The economic constitution idealistic values faced with an open market regulation, control and supervision of a force that is not only submitted to the Constitutional Court ruling which has the character of final appeal.